EVALUATION OF EFFECT OF DHANYAK CHURAN IN UPPER G.I.T. DISORDERS IN PREGNANCY W.S.R TO GARBHAJ CHHARDI - Kumar Meena, Narendra (AYUSHDHARA, 2017)
Motherhood is a greatest gift to women which is presented by good to see becomes a mother of a healthy child women, who goes through motherhood experience that is a cause of proud being a mother. The pregnancy is a state of so many physiological changes by which the pregnant women may suffer so many problems out of which the G.I.T. Tract problems like nausea, Vomiting, Headache, Heart burn, constipation etc are more effective etiological treats to disturb the health of mother and child. The aim of this research work is to assess the efficacy of Dhanyaka Churna in upper GIT disorders w.s.r. Gharbhaj Chhardi. Ayurveda is a treasure of herbal drugs. India recently increased research on traditional Ayurvedic herbal medicines after observation. Study design: The study was single grouped, which contains 20 female patients selected from OPD/ IPD of M.M.M Govt. Ayurveda College & Hospital, Udaipur (Rajasthan). Drugs containing (Dhanyaka churana + Sarak) with Tandulodak. Tandulodaka use as a Anupana with Sangrahaka. Drugs. dose 2gm bd. The regimen followed for 45 days with follow up every 15 days. Base line assessment was done of selected patients. Result: The study result suggests that The Dhanyaka churna with Tandulodak is effective in Headache Loss of appetite, Nausea, Vomiting and Giddiness during pregnancy.